Technology Computer Vision Detects Plastic Waste Objects in Public Areas Using YOLOv8 - Tomasila, Golda; Marthevienty H.T Soumokil; Kezya Therssya Nanlohy, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
The increasing volume of plastic waste that continues to increase from year to year has the potential to damage the environment and endanger public health. Various waste handling efforts are carried out manually to sort the types of plastic waste in several public areas. Public areas are places of activity that have the potential to have a lot of plastic waste. Where the purpose of this study is to apply computer vision technology for the detection of plastic waste objects in public areas using YOLOv8. The results of this research are expected to contribute to more modern and efficient waste management efforts. Where the automatic detection system of plastic waste objects can make a scientific contribution to the development and application of computer vision technology in the environment.